Language Culture of Loan Words in Lao Language Dictionary: https://doi.org/10.69692/SUJMRD0901319 - DUANGCHAN, Boy; SAYVONGSAN, Chanthaphone; NIMNUAN , Laion; NORDALA , Phouvong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The research simed to investigates the loan words from the Pali language that appears in the Lao language dictionary and to categorize its language culture that appears in the language dictionary. The study was conducted through an analysis of the loan words from the Pali language that appears in the Lao language dictionary to classify the words based on the cultural characteristics of the language, according to the Voegelins’ language culture division. The results revealed that there are 3,695 loan words from the Pali language. They are divided into four main categories: 1) nature, 2) human and human behavior, 3) wisdom, emotions, feelings and values, and 4) individual relationship. The loan words based on Voegelins’ language culture division, can be concluded as follows: the category of wisdom, emotions, feelings, and values takes the highest proportion with the number of 1,355 words, accounting for 36.67 per cent. There are 926 words about the religiousness, legends, beliefs, rituals, ceremonies, instruments, and the places for ceremony, accounting for 25.06 per cent. There are 617 words in the human beings and human behavior category, accounting for 16.69 per cent. However, there are only 27 words about dressing, accessories, hats, hairstyles, shoes and care accounting for 0.73 per cent.